GAMIFICATION AS A METHOD OF SOCIAL MANAGEMENT - Pavel Evgenevich Serkin; Nadezhda Evgenevna Serkina (Вестник Майкопского государственного технологического университета, 2023)
The relevance of the research is due to the imbalance and high level of systemic risks accompanying the development of postmodern society. One of the ways to rationalize the stochastic and heuristic factors of social development of post-modern society is the sociological concept of gaming, which is applicable both at the society level as a whole and for one of its key institutions - the institute of social management, which ensures the stability of social development in the conditions of bifurcation and systemic risks of modern technogenic Western civilization. The methodological basis of the research is the so-called. Bourdieu’s “structuralist constructivism”, recognizing the interdependence of objective social structures and social practices of actors, on the one hand, and the existence of some matrices of a social action of an individual, determining its practical ability to construct social objects, on the other hand. Using the concept of game habit and P. Bourdieu’s social fields, the authors point out the possibility and relevance of the use of gaming techniques in the social management system, the reflexivity of the social subject and the rejection of the rigid dictatorship of social institutions becomes one of the social actor's life strategy in postmodern society. The authors conclude that the use of the gamification method in social management allows to rationalize the stochastic factors of social evolution and to increase the efficiency of performing one of the central functions of the institute of social management, that is ensuring the sustainable development of society.